Coherence Among Sectors and Stakeholders Differentiates Districts in Rwanda That Did and Did Not Improve Child Stunting. (29th May 2020) - Iruhiriye, Elyse; Olney, Deanna; Frongillo, Edward
Abstract: Objectives: Focusing on national trends can mask sub-national differences in reducing undernutrition. Using qualitative data, we aimed to understand differences in stunting reduction rates in Rwanda through the roles of commitment to improve nutrition and coherence across sectors and administrative levels in implementing Rwanda's multisectoral nutrition policy. Methods: For this study, we purposefully selected 5 districts in which stunting decreased (reduced) and 5 where it increased or stagnated (non-reduced). We conducted 58 semi-structured interviews with district leaders ( n  = 38) and frontline workers ( n  = 20) from sectors involved in implementing Rwanda's nutrition policy. Interviews focused on topics related to commitment and coherence in nutrition. Responses were coded to capture themes on changes and challenges in commitment and coherence and were compared between reduced and non-reduced districts. Results: Respondents from reduced districts were more likely to define commitment to nutrition as optimal implementation of policy whereas those from non-reduced districts tended to focus more on financial commitments to improving nutrition. Differences in coherence between the two district types mainly revolved around the implementation of Rwanda's District Plans to Eliminate Malnutrition (DPEMs). Respondents from reduced compared to non-reduced districts were more likely to report optimal DPEM implementation, including regularly conducting nutrition planning meetings, using data from different sectors to assess plans and progress in improving nutrition outcomes, and having better integration of the agriculture and nutrition sectors. In contrast, respondents from non-reduced districts were more likely to report limitations in their relationships with various national level stakeholders and in their nutrition and/or monitoring and evaluation (M&E) capacities. In turn, several people in non-reduced districts requested additional training on these topics. Conclusions: Coherence among sectors and stakeholders and capacity in nutrition and M&E were stronger in reduced districts. Enhancing these in non-reduced districts may lead to greater stunting reduction. Funding Sources: The Dutch Government through SNV and the Voice for Change Partnership Programme (V4CP) and A4NH led by IFPRI.